2019
DOI: 10.1021/acsabm.9b00748
|View full text |Cite
|
Sign up to set email alerts
|

Electrical Field Reversibly Modulates Enzyme Kinetics of Hexokinase Entrapped in an Electro-Responsive Hydrogel

Abstract: In this paper, the potential use of electroresponsive poly(acrylic acid) (PAA) gels as reversible enzyme activity regulators is analyzed. This was evaluated by measuring the glucose conversion by hexokinase embedded PAA hydrogels under external electrical stimuli. Hexokinase physically entrapped within PAA gels showed a significant increase in activity under an electrical stimulus as compared to in the absence of a stimulus. Kinetic studies revealed that the change in reaction rate could be attributed to the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…showed that the accessibility of the substrate toward the active site of hexokinase (HK) entrapped in an electroresponsive hydrogel was altered upon application of an electrochemical potential due to the reversible contraction and expansion of the hydrogel. 104 The reaction kinetics of enzymes can also be modified by trapping enzymatic cascades in a porous conducting metal oxide electrode material. This was done by Morello et al to reversibly recycle a nicotinamide cofactor that was generated with an enzymatic cascade consisting of ferredoxin NADP + reductase, L-malate NADP + oxidoreductase, fumarase, L-aspartate ammonia-lyase, and carbonic anhydrase.…”
Section: Electrochemical Controlmentioning
confidence: 99%
“…showed that the accessibility of the substrate toward the active site of hexokinase (HK) entrapped in an electroresponsive hydrogel was altered upon application of an electrochemical potential due to the reversible contraction and expansion of the hydrogel. 104 The reaction kinetics of enzymes can also be modified by trapping enzymatic cascades in a porous conducting metal oxide electrode material. This was done by Morello et al to reversibly recycle a nicotinamide cofactor that was generated with an enzymatic cascade consisting of ferredoxin NADP + reductase, L-malate NADP + oxidoreductase, fumarase, L-aspartate ammonia-lyase, and carbonic anhydrase.…”
Section: Electrochemical Controlmentioning
confidence: 99%
“…Moreover, there was an absorption peak of amides at 1538 cm -1 in the spectra of the products which was absent in the spectra of PAA, indicating the successful formation of enzyme-PAA conjugates. [60,[63][64][65] It is worth noting that enzyme-alginate conjugates cannot be prepared via EDC/NHS coupling strategy (Supporting Information Figure S4). The enzyme cannot covalently bind to alginate which may be ascribed to the steric hindrance of the cyclic structure to the coupling reaction of COOH in alginate.…”
Section: Preparation Of Microfibers and Encapsulation Of Proteins/enz...mentioning
confidence: 99%
“…Lysine Light; temperature; pH Deoxyribonuclease I (DNase I); [1b] peroxidase (HRP); [3a] trypsin, papain, DNase I; [10] lysozyme; [45] glucoamylase (GA), proteinase K (ProK), and horseradish RNase; [46] microperoxidase-11; [47] lipase; [48] chymotrypsin [49] Site-selective covalent modification Tyrosine Temperature, pH, GSH Horseradish peroxidase [ 23a] Noncovalent modification / PEGylation, electrical field 𝛼-amylase; [50] glucose; [51] selenoenzyme; [52] dehydrofolate reductase [53] Creation of a switchable reaction center…”
Section: Nonspecific Covalent Modificationmentioning
confidence: 99%